Hubungan Bermain Game Online Terhadap Kualitas Tidur Dan Prestasi Belajar: Studi Pada Siswa Smpn 1 Damai, Kutai Barat - Rosalina Tandilino Liku; Parellangi Parellangi; Amiruddin Amiruddin (Poltekkes Kemenkes Kalimantan Timur, 2024)
Online gaming has become an increasingly prevalent phenomenon in Indonesia, especially among teenagers and school-aged children. This study aims to examine the relationship between online gaming, sleep quality, and academic performance among students of SMPN 1 Damai, West Kutai Regency. This research employed a descriptive correlational design with a retrospective approach, conducted from February to March 2022. The population consisted of students from grades VII to IX, with a total of 82 respondents selected using consecutive sampling. The statistical test used was the Chi-Square test. The results showed that the majority of respondents had a low intensity of online gaming (85.4%). Most respondents' sleep quality was categorized as good (63.4%). Academic performance was categorized as good and fairly good (39.0%). Statistical analysis revealed a significant relationship between online gaming and sleep quality (p-value = 0.001 < 0.05) and between online gaming and academic performance (p-value = 0.001 < 0.05). In conclusion, there is a significant relationship between online gaming intensity, sleep quality, and academic performance among students of SMPN 1 Damai, West Kutai Regency.